2019
DOI: 10.1111/ijfs.14403
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive constituents, in vitro radical scavenging and antibacterial activities of selected Apis mellifera honey from Kenya

Abstract: Summary There is limited information about the relative composition and health benefits of various honey consumed across Africa. This study aimed at estimating the bioactive constituents, in vitro radical scavenging and antibacterial activities of 16 kinds of honey obtained from different geographical locations in Kenya. Manuka 5 + honey was included for comparison. Some of the tested honey had biochemicals and bioactivities similar to or higher than Manuka 5 + honey. The honey exhibited DPPH radical scavengin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
3
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 48 publications
0
32
3
2
Order By: Relevance
“…They were determined using the method of Dowd as in published procedures (Mokaya, Bargul, Irungu, & Lattorff, 2020). Briefly, 1 ml extract of the sample (1 g of honey in 4 ml of water) was mixed with 4 ml of distilled water, then 300 µl of 5% NaNO 2 was added and mixed.…”
Section: Total Flavonoids Content (Tfc)mentioning
confidence: 99%
See 1 more Smart Citation
“…They were determined using the method of Dowd as in published procedures (Mokaya, Bargul, Irungu, & Lattorff, 2020). Briefly, 1 ml extract of the sample (1 g of honey in 4 ml of water) was mixed with 4 ml of distilled water, then 300 µl of 5% NaNO 2 was added and mixed.…”
Section: Total Flavonoids Content (Tfc)mentioning
confidence: 99%
“…They were quantified following the Folin-Ciocalteu method as described in published protocols (Mokaya et al, 2020). One gram of honey was diluted with 20 ml of distilled water.…”
Section: Total Phenols Content (Tpc)mentioning
confidence: 99%
“…The World Health Organization (WHO) has since called for urgent corrective actions including expansion of effective antibacterial therapies [7]. Combined with the higher demand for better quality food with consistent qualities, the search for foods naturally rich in bioactive compounds showing broad antibacterial activities has since been stepped up [8]. Studies have shown that raw H. itama honey is a possible candidate for the complementary treatment to combat AMR, following numerous claims of its excellent antibacterial activity against many superbugs [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…According to Ewnetu et al [62], stingless bee honey has higher antibacteri-al effects than Apis mellifera honeys. In western Kenya, Apis mellifera honey has been reported to possess antibacterial effects against E. coli [63]. However, no stingless bee honey has been explored for comparison purposes hence the purpose for this study.…”
Section: Discussionmentioning
confidence: 99%